The complete letters of Henry James - James, Henry,Anesko, Michael,Zacharias, Greg W.,Sommer, Katie,Poole, Adrian (University of Nebraska Press, 2020)
This fourteenth installment in the complete collection of Henry James's more than ten thousand letters records James's ongoing efforts to care for his sister, develop his work, strengthen his professional status, build friendships old and new, and maximize his income
9781496221124
Keywords: James; Henry; Authors; American